IJSIE ABSTRACTS - Kananga Mukuna (International Journal of Studies in Inclusive Education)
The International Journal of Studies in Inclusive Education (IJSIE) is a double-blinded, peer-reviewed, fully open-access journal providing an advanced platform and opportunities for inclusive education-related research outputs. The Editorial Board welcomes empirical, conceptual, academic, and theoretical articles critically analysed and interpreted in all its holistic approach to inclusive education: inclusive education, learning barriers, learners, or students with special needs, etc. The scholarly articles must be prepared, treated, and interpreted with the same academic rigor expected of academic research. The IJSIE aims to provide an interdisciplinary forum for scholars, publishing professionals, librarians, and others to communicate original research that addresses current issues informed by the best practices. Scholarly publishing has only recently begun to exploit the full potential of networked digital technologies, which affects the broader process of research communication, including public access to and engagement with research. Influential trends towards responsible research and innovation, the globalisation of research, the emergence and inclusion of new or previously excluded stakeholders, and the advent of open science are reshaping scholarly publishing's scope and nature. The social, legal, and ethical dimensions of publications continue to co-evolve with these changes. Publications aim to provide an interdisciplinary forum for scholars, publishing professionals, librarians, and others to communicate original empirical and theoretical research on these and related topics to address current issues and inform best practices. The IJSIE publishes research, reviews, scholarly writings, and reports concerning the inclusion of learners (students) with special learning needs in mainstream classrooms (schools) . The IJSIE is focused on inclusion issues in all educational endeavours, such as research, administrative issues, teaching and learning in classrooms, and inclusion of students at higher institutions. The IJSIE defines inclusive education within the broad context of the Salamanca statement guidelines. Special Education has within its heritage the perspectives of advocating for persons with exceptionalities and embracing individual differences. The IJSIE is an inclusive education publication in the GAERPSY. It relies on vast theoretical, practical, and thematically scholarly inclusive education, including unpublished research in human behavioural issues. These include at-risk learners, mental well-being, psycholinguistics, and inclusive education.